Makna Journaling bagi Generasi Z - Tia Habibah Dwitami; Ratri Rizki Kusumalestari (UNISBA Press, 2023)
Abstract. As Generation Z is accustomed to living with digital technology and social media, there is an unique phenomenon called journaling among them. Journaling is a new term popular among Generation Z to refer to writing activities such as diaries. This research on